2018
DOI: 10.1177/0956797618799300
|View full text |Cite
|
Sign up to set email alerts
|

First Impressions of Personality Traits From Body Shapes

Abstract: People infer the personalities of others from their facial appearance. Whether they do so from body shapes is less studied. We explored personality inferences made from body shapes. Participants rated personality traits for male and female bodies generated with a three-dimensional body model. Multivariate spaces created from these ratings indicated that people evaluate bodies on valence and agency in ways that directly contrast positive and negative traits from the Big Five domains. Body-trait stereotypes base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 36 publications
1
70
0
Order By: Relevance
“…Regarding the stimuli that we used, while the design of Studies 4–6 anticipate possible confounds between weight and physical attractiveness (as highlighted by Nickson et al [79]), future research will be needed that more clearly disentangles the degree to which perceived differences in strength might have influenced participant ratings. The stimulus-set that we used in Studies 4–6 does follow the conventional depictions of under-, normal-, and over-weight developed by Singh [73,74] and clearly controls for height; however, it is plausible that more varied stimuli (e.g., with different body shapes such as the 3-D images explored by Hu et al [88]) could generate different patterns of ratings. Indeed, this is sensible in light of the fact that there remain substantial gaps in how the relationships between height and weight are understood [62] along with our own expectation that the positive relationship that we find in Studies 4–6 between height and perceived persuasiveness must eventually have an upper limit after which the relationship would be curvilinear.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the stimuli that we used, while the design of Studies 4–6 anticipate possible confounds between weight and physical attractiveness (as highlighted by Nickson et al [79]), future research will be needed that more clearly disentangles the degree to which perceived differences in strength might have influenced participant ratings. The stimulus-set that we used in Studies 4–6 does follow the conventional depictions of under-, normal-, and over-weight developed by Singh [73,74] and clearly controls for height; however, it is plausible that more varied stimuli (e.g., with different body shapes such as the 3-D images explored by Hu et al [88]) could generate different patterns of ratings. Indeed, this is sensible in light of the fact that there remain substantial gaps in how the relationships between height and weight are understood [62] along with our own expectation that the positive relationship that we find in Studies 4–6 between height and perceived persuasiveness must eventually have an upper limit after which the relationship would be curvilinear.…”
Section: Discussionmentioning
confidence: 99%
“…Humans do not make decisions in isolation of other factors [45]. Without conscious awareness, people incorporate irrelevant information into a variety of decisions such as first impressions, personality trait judgments, and jury decisions [21,29,90,91]. Even when provided identical information, the context, a person's biases, and the way in which information is presented influences decisions [4,15,17,23,36,43,68,94].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Aviezer, Trope, & Todorov, 2012a demonstrated that body context plays an important role in differentiating between positive and negative extreme emotions, and other studies have shown that faces and bodies are processed holistically when judging emotions (for example Aviezer, Trope, & Todorov, 2012b;Meeren, van Heijnsbergen, & de Gelder, 2005;Van den Stock, Righart, & de Gelder, 2007). Using advanced modeling tools, recently body shape features such as weight or having a rectangular/pear shaped body, have been shown to predict body-based personality trait inferences as well (Hu, Parde, Hill, Mahmood, & O'Toole, 2018).…”
Section: Introductionmentioning
confidence: 99%